Without solving, examine the nature of the roots of the equations 2x² - 6x + 3 = 0.

We need to examine the nature of the roots of the equations 2x² – 6x + 3 = 0.

This can be done by finding the discriminant of the equation.

2x2 – 6x + 3 = 0

Comparing the given equation with general form of equation: ax2 + bx + c = 0, we get;

a = 2, b = – 6, c = 3

b2 – 4ac = (- 6)2 – 4(2)(3)

= 36 – 24

= 12

b2 – 4ac > 0

Thus, the equation has two distinct real roots.

Since,

x = [- b ± √ (b2 – 4ac)] / 2a

x = [-(- 6) ± √12] / (2)2

= (6 ± 2√3) / 4

= (3 ± √3) / 2

Roots of the given equation are x = (3 + √3) / 2 and x = (3 – √3) / 2

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question